2005
DOI: 10.1099/mic.0.27709-0
|View full text |Cite
|
Sign up to set email alerts
|

Statistical assessment of a laboratory method for growing biofilms

Abstract: Microbial biofilms have been grown in laboratories using a variety of different approaches. A laboratory biofilm reactor system, called the CDC biofilm reactor (CBR) system, has been devised for growing biofilms under moderate to high fluid shear stress. The reactor incorporates 24 removable biofilm growth surfaces (coupons) for sampling and analysing the biofilm. Following preliminary experiments to verify the utility of the CBR system for growing biofilms of several clinically relevant organisms, a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
178
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(181 citation statements)
references
References 15 publications
2
178
0
1
Order By: Relevance
“…This system has been heavily used to identify potential anti-biofilm agents, by measuring the reduction in surface attached biomass on the sides of wells after treatment with potential therapeutic agents [51][52][53][54]. In addition to this, The Center for Disease Control (CDC) approved biofilm reactor [55][56][57], and drip flow reactors, have proved excellent for assessing biofilm formation on biological and non-biological materials [58][59][60]. These flow systems and microtitre assays are the workhorses of in vitro biofilm research, and have generated a phenomenal amount of data that has greatly expanded our knowledge about how bacteria attach and differentiate into mature biofilms in vitro.…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This system has been heavily used to identify potential anti-biofilm agents, by measuring the reduction in surface attached biomass on the sides of wells after treatment with potential therapeutic agents [51][52][53][54]. In addition to this, The Center for Disease Control (CDC) approved biofilm reactor [55][56][57], and drip flow reactors, have proved excellent for assessing biofilm formation on biological and non-biological materials [58][59][60]. These flow systems and microtitre assays are the workhorses of in vitro biofilm research, and have generated a phenomenal amount of data that has greatly expanded our knowledge about how bacteria attach and differentiate into mature biofilms in vitro.…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…Other differences include the liquid flowing over the surface. During in vitro biofilm growth, well-defined minimal medias are most often used [49,56,57,71,72]. In catheters, the liquids flowing over the surface could be urine, blood or other bodily fluids, which constitutes a very different growth environment for bacteria.…”
Section: In Vitro Investigation Of Biofilmsmentioning
confidence: 99%
“…The SOPs proposed for biofilm studies are specific for: the growth of reproducible mixed biofilms of P. aeruginosa (ATCC#700829), Pseudomonas fluorescens (ATCC# 700830) and Klebsiella pneumoniae (ATCC#700831), analyzed in terms of structure and viable cell counts using a flat-plate, open channel reactor (Jackson et al 2001); the growth of P. aeruginosa biofilm using the CDC biofilm reactor (CBR) system (Goeres et al 2005); the assessment of resistance of Staphylococcus aureus biofilm cells to disinfectants (Luppens et al 2002); and the optimized quantification of enterococci biofilms using microtitre-plates (Extremina et al 2011). Also, as a first step towards the establishment of a SOP for methods of analysis, several authors have studied and compared methods in use on biofilm related research for evaluating biofilm disinfectant efficacy with different fluid dynamics (CDC, drip flow and static biofilm reactor systems) (Buckingham-Meyer et al 2007), comparing methods for quantification of microbial biofilms grown in microtiter plates (crystal violet (CV), Syto9, fluorescein diacetate (FDA), resazurin, XTT and dimethyl methylene blue (DMMB) assays) (Peeters et al 2008), and checking the validity of the harvesting and disaggregating steps (Hamilton et al 2009).…”
Section: Standardization Of Laboratory Proceduresmentioning
confidence: 99%
“…Indeed, statistical analysis performed by Goeres [25] demonstrated that the CDC biofilm reactor system serves as a reliable experimental tool to study biofilm formation evolving from a wide range of organisms.…”
Section: Abbreviations: Ss Stainless Steelmentioning
confidence: 99%